SIMULASI PENGGUNAAN FILTER AKTIF SHUNT DENGAN KONTROL PI UNTUK MEREDAM TOTAL HARMONIC DISTORTION (THD) PADA GEDUNG DH TEKNIK ELEKTRO UNIVERSITAS UDAYANA - Kresna Dharma Yudha, A.A. Gede; Indra Partha, Cok. Gede; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p18, 2023)
Every daily activity requires electrical energy. Electrical energy loads vary. Harmonic distortion is one of the results of current and voltage wave disturbances caused by non-linear loads, such as lamps, computers, and air conditioners, among others. This causes a decrease in the quality of electric power. High resonance disturbances can cause increased harmonics which can reach 4 to 10 times under full charge conditions. One way to overcome harmonic disturbances is by using a harmonic filter. In this study, an active shunt filter with PI control is used to reduce harmonic resonance disturbances. The THD value according to the IEEE 519-2014 standard is obtained by using this harmonic filter. In this study using Matlab Simulink simulation software. The THD obtained before the simulation was carried out, namely THDv in the R phase = 1.62%, S = 1.64%, T = 1.71%, THDi in the R phase = 14.73%, S = 12.96%, T = 13.53%. The THD obtained after the simulation is THDI at each phase R = 3.29%, S = 3.01%, T = 4.53%.